Assessing how Physical Education Faculty Behaviors Affect College Student Perceptions of Them as Health Instructors: Do we Practice What we Teach? - John Lothes II (The Ohio State University Libraries, 2019)
Background: While there is a large body of evidence on faculty as role models, there is scant research on physical education faculty and how their behaviors may be reflected and internalized in student health perceptions. Aim: To determine the impact of physical education faculty health behaviors on student perceptions. Method: Surveys were administered among college students enrolled in a number of Physical Education (PED 101) courses at a university in the southeast United States. Different vignettes (healthy versus unhealthy behaviors) were provided describing scenarios where students may observe their physical education faculty both on and off campus. Scenarios were assessed to examine how there may be an effect on the student's perception as either favorable or unfavorable of faculty as a health instructor. Results: Both salient behaviors (e.g., seeing faculty exercising on campus or drinking water during class) and non-salient cues (e.g., having a grocery cart full of health or unhealthy foods at the store) both play a role in students' perceptions. Conclusion: Physical Education faculty must be aware that behaviors they engage in both in the classroom and out of the classroom may shape how students perceive them.